Isolasi dan Pertumbuhan Miselium Jamur Grigit (Schizophyllum Commune) Pada Berbagai Media Biakan Murni - Yeni Yeni; Nanang Wahyu Prajaka; Fahri Ali; Abied Khafidhan; Ratih Rahhutami; Raissa Tazkia Nurhaliza; Desty Aulia Putranti (Jurnal Penelitian Pertanian Terapan, 2026)
The split gill mushroom (Schizophyllum commune) is an edible fungus that can be readily identified by its distinctive morphology and has considerable potential for development as a food source and a producer of bioactive compounds in Indonesia. Consequently, the establishment of an efficient propagation method through pure culture is essential. This study aimed to isolate S. commune and to evaluate its mycelial growth on different pure culture media. Isolation was conducted using a tissue culture technique from healthy and fresh fruiting bodies. The culture media evaluated were Potato Dextrose Agar (PDA), rice washing water medium, coconut water medium, rice bran medium, and corn boiling water medium. Mycelial growth rate, radial growth diameter, and mycelial morphological characteristics were used as growth parameters. The results indicated that the type of culture medium significantly influenced the mycelial growth of S. commune. PDA, rice washing water, and rice bran media supported the highest and most uniform mycelial growth. Mycelia grown on PDA and rice bran media exhibited a whitish-yellow coloration, dense and uniform growth, and a cotton-like texture. These findings suggest that both conventional and alternative media derived from locally available resources can effectively support the pure culture of S. commune, offering potential for more cost-effective and sustainable cultivation practices.